COMMENTS ON CHANGES IN THE STRUCTURE OF HIGHER EDUCATION IN POLAND – CONDITIONS AND RESULTS (Research Bulletins of the Faculty of Economic Sciences, 2024)
The aim of the article is to understand the determinants of changes in the structure of higher education in Poland after 1989 and to present their general effects. The literature searched for turning points that Polish higher education experienced after 1989. It was shown that political changes directly influenced the transition of the higher education system towards the free market, which resulted in the launch of private universities. The mixed structure of the higher education system, i.e. the simultaneous operation of public and private universities, introduced competitive mechanisms in which the student recruitment mechanism was important. The article conducted empirical research, focusing on the quantitative presentation of the overall effects of changes in the structure of higher education in Poland in the years 1992-2021 in terms of changes in the number of students. The analysis used statistical inference based on the results of regression analysis. The results of the study on the number of students in Poland indicate that in a situation of growing demand for higher-level educational services, non-public universities were characterized by higher recruitment dynamics and were more competitive compared to public universities. However, in a situation of decreasing demand, they were unable to cope with the competition from public universities – they lost students faster.
Keywords: political transformation, higher education system, university, student, Poland